MHD mixed convection stagnation-point flow of a chemically reacting fluid over a plate in a porous medium with radiation / Niranjan Hari - Niranjan , Hari (2016)
This thesis deals with the extensive analysis on mathematical modelling of mixed convective flow, heat and mass transfer over a vertical plate embedded in a porous medium near the stagnation point with various effects, such as MHD, slip, chemical reaction, radiation, heat generation/absorption, soret and dufour effects. The working medium is an incompressible, Newtonian, viscous and electrically conducting fluid. A stagnation point occurs whenever a flow impinges on a solid object and it holds the highest pressure. The fluid divided into two streams when the fluid hits at stagnation point and the viscous flow adheres to the plate. The uniform magnetic field is applied in the direction normal to the vertical plate. Since the magnetic Reynolds number is too small, the induced magnetic field is negligible. There is no Hall effect and Joule heating. The porous medium is modeled by Darcy’s law and the porous medium is isotropic and homogeneous. The porous medium is in thermodynamic equilibrium with the local fluid. All the fluid properties are taken as constant except the density in the buoyancy term. The physical problem is modelled mathematically by using principles of mass, momentum, energy and species concentration. The governing coupled nonlinear partial differential equations are converted into a system of non-linear ordinary differential equations by using similarity transformation. Then, ordinary differential equations are solved numerically by shooting method along with fourth-order Runge-Kutta integration. The local skin friction, Nusselt number and Sherwood number are calculated and exposed comprehensively. In order to ascertain the accuracy of numerical results, the present results are compared with previously published work and they are found to be in good agreement. The results are depicted in the form of velocity, temperature and concentration profiles for different combination of pertinent parameters involved in the study.